PENGEMBANGAN LKM BIOLOGI DASAR BERORIENTASI PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS MAHASISWA - Saidil Mursali; Safnowandi Safnowandi (Bioscientist : Jurnal Ilmiah Biologi, 2016)
Abstract: This study aims to (1) develop the basic Biology LKM-oriented inquiry learning; (2) describe the implementation of Basic Biology learning by using an inquiry-oriented LKM; (3) to describe students' science process skills in Basic Biology learning by using LKM-oriented inquiry learning, and (4) to describe the student's response in Basic Biology learning activity using LKM-oriented learning inquiry. This research is a kind of developmental research, using 4-D model and implementation design using one group pretest-postest. Data to be collected include data of science process skill and student response, with data analysis technique is descriptive qualitative and quantitative. The developed Basic Biology LKMs have validity with reasonable and reliable categories, so they can be used in learning. The results of the implementation of learning tools, including: the implementation of RPS categorized very well, students' science process skills are generally well categorized and experienced an increase with N-gain reaching 0.55 medium category, as well as good student response. Overall it can be concluded that the basic Biology LKM oriented inquiry learning can improve students' science process skills.